JURNAL PENGABDIAN MASYARAKAT PENGADAAN RUMAH BELAJAR UNTUK MENINGKATKAN MINAT BELAJAR SISWA/I SDN 003 KEPENUHAN - H. R. Usman Rery; Bangkit Wahidi; Dinni Yunike Jasril; Erva Roudhotul Jannah; Finoriza Syahputri Akbar; Maysheila Ulandhary; Nikita Sukmadewi Sakura Nasution; Rendika Adisman; Reni Yolanda; Tia Dwi Ananda (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This study examines the low interest in learning in students in the learning process at school. The purpose of this research is to increase students' interest in learning through the provision of learning houses. The research subjects are students of SDN 003 Kepenuhan from class I to class VI. Data collection techniques were through observation and interviews. The results showed an increase in students' interest in learning based on data on increasing student abilities before and after the opening of the learning house. This study was declared to have met the success requirements above 80% of the initial conditions before the opening of this learning house